Of landscape quality and landscape character: The evolution of landscape assessment in the UK and it's potential application in Austria - Michlmayr-Gomenyuk, Julia; Stiles, Rihard (4D Journal of Landscape Architecture and Garden Art, 2014)
Landscape, as the European Landscape Convention defines it, is “an area as perceived by people”. But it is not just people as individuals who perceive landscape. People also create institutions and organisations and they in turn have their own perceptions, especially of something as complex and multi-dimensional as landscape. This paper will, amongst other things consider the way in which the perceptions embodied in the terms of reference of institutions and organisations influence the way in which they approach landscape.
Keywords: landscape quality; landscape character; European Landscape Convention; landscape; naturpark; nature conservation